Constructed fragilities: gender and susceptibility to smallpox in the Modern Age (Ágora Journal, 2026)
This article examines the intersection of gender and susceptibility to smallpox during the Early Modern period, highlighting how social and cultural constructions influenced women's experiences and perceptions of the disease. Smallpox, endemic in Europe from the 15th century onwards, not only posed significant health risks, but also shaped social dynamics, especially with regard to female roles and identities. Through an analysis of historical texts and medical practices, the study reveals how prevailing gender norms and medical theories, rooted in humoral medicine, contributed to the stigmatization and marginalization of women. Ultimately, this research highlights the importance of understanding the social dimensions of illness and the ways in which gendered experiences have shaped public health narratives throughout history.
Keywords: gender; smallpox; Modern Age.